Gaze behaviour in basketball jump shot: Differences between expert and non-expert athletes - Marques, R. C. A.; Mendes, R. S. M.; Martins, F. M. L.; Gomes, R. M. M.; Coelho-E-Silva, M. J.; Dias, G. N. F. (South African Journal for Research in Sport, Physical Education and Recreation, 2021)
The aim of this study was to compare the visual patterns of basketball players of two different levels (Under-16 vs. Senior). Twenty athletes, 10 U16 (15.2±0.4 years and 7.1±2.5 years of practice) and 10 Senior (27.6±3.7 years and 18. 4±4.6 years of practice) made a total of 50 jump shots in ten different positions (shooting angles of 0º, 45º, 90º, 135º and 180º and at distances of 6.80m and 4.23m, in each of the shooting angles). Measures of unpredictability or irregularity in biological time series were analysed through the Coefficient of Variation (CV%) values of Shannon`s Entropy. Results show that gaze behaviour of both age groups is characterised by an average dispersion (CV% values between 18 and 27). However, senior players presented greater jump shot efficacy compared to U16 (64.0% vs. 41.8%) and global mean values slightly lower than the U16 in the Shannon`s Entropy results. The visual patterns did not differ neither between the two groups nor between the shooting distances of the jump shots.